2023
DOI: 10.1111/jcmm.17754
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D may alleviate pre‐eclampsia by modulating the ferroptosis signalling pathway: A hypothesis based on recent literature

Abstract: Ferroptosis is a novel form of regulated cell death typically characterized by non‐apoptotic, iron‐dependent, and reactive accumulation of oxygen species. Recent studies have found that ferroptosis plays an important role in the pathophysiology of pre‐eclampsia (PE). In order to find potential therapeutic targets for ferroptosis intervention and better prevent the occurrence and progression of PE, the signalling pathways that regulate ferroptosis need to be identified. In this article, we review the role of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, further studies are needed to investigate the specific involvement of ferroptosis in T2DM. The previous review summarized that vitamin D might modulate the ferroptosis signaling pathway [29][30][31][32]. Therefore, vitamin D may play a vital role in alleviating T2DM by modulating the ferroptosis signaling pathway.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…In addition, further studies are needed to investigate the specific involvement of ferroptosis in T2DM. The previous review summarized that vitamin D might modulate the ferroptosis signaling pathway [29][30][31][32]. Therefore, vitamin D may play a vital role in alleviating T2DM by modulating the ferroptosis signaling pathway.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…Vitamin D (VD) is a fat-soluble steroid that is a key regulator of calcium and phosphorus metabolism ( Holick, 2007 ), which mainly circulates to form 25-hydroxyvitamin D3 [25 (OH)D3]. Recently, studies have found that VD plays a vital role in development of depression ( Kaviani et al, 2020 ), irritable bowel syndrome (IBS) ( Alvi et al, 2022 ), type 1 diabetes mellitus ( Liu et al, 2015 ), and obesity ( Yu et al, 2023 ; He et al, 2023 ; Li et al, 2023 ). Current research suggests that VD can interfere with a plethora of cellular mechanisms and directly or indirectly modulate the microbiota ( Tangestani et al, 2021 ), release antimicrobial peptides, and modulate the immune system and inflammatory processes ( Song et al, 2023 ) this, in turn, can actively interfere with changes in gut function.…”
Section: Introductionmentioning
confidence: 99%